Arthropod-bacteria interactions influence assembly of aquatic host microbiome and pathogen defense - Greenspan, Sasha E.; Lyra, Mariana L. [UNESP]; Migliorini, Gustavo H. [UNESP]; Kersch-Becker, Monica F.; Bletz, Molly C.; Lisboa, Cybele Sabino; Pontes, Mariana R.; Ribeiro, Luisa P.; Neely, Wesley J.; Rezende, Felipe; Romero, Gustavo Q.; Woodhams, Douglas C.; et al. (Royal Soc, 2019)
The host-associated microbiome is vital to host immunity and pathogen defense. In aquatic ecosystems, organisms may interact with environmental bacteria to influence the pool of potential symbionts, but the effects of these interactions on host microbiome assembly and pathogen resistance are unresolved. We used replicated bromeliad microecosystems to test for indirect effects of arthropod-bacteria interactions on host microbiome assembly and pathogen burden, using tadpoles and the fungal amphibian pathogen Batrachochytrium dendrobatidis as a model host-pathogen system. Arthropods influenced host microbiome assembly by altering the pool of environmental bacteria, with arthropod-bacteria interactions specifically reducing host colonization by transient bacteria and promoting antimicrobial components of aquatic bacterial communities. Arthropods also reduced fungal zoospores in the environment, but fungal infection burdens in tadpoles corresponded most closely with arthropod-mediated patterns in microbiome assembly. This result indicates that the cascading effects of arthropods on the maintenance of a protective host microbiome may be more strongly linked to host health than negative effects of arthropods on pools of pathogenic zoospores. Our work reveals tight links between healthy ecosystem dynamics and the functioning of host microbiomes, suggesting that ecosystem disturbances such as loss of arthropods may have downstream effects on host-associated microbial pathogen defenses and host fitness.
Keywords: amphibian; arthropod; Batrachochytrium dendrobatidis; chytridiomycosis; disease; host microbiome